Genetic Relationship among Nepalese Rice Landraces and Cultivars based on RAPD Markers - Joshi, Bal K; Bimb, Hari P; Kansakar, David; Ghimire, Ekta (Nepal Journal of Biotechnology, 2012)
Genetic information of any genotype is necessary to manage and utilize them in conservation and breeding program. A total of 28 RAPD markers were used to relate the genetic structure among 50 Nepalese rice genotypes consisting of 29 landraces, 12 breeding lines and 9 released cultivars. Some of them are aromatic and blast resistance. Only four primers (P41, P60, P109 and P141) amplified the DNA of these genotypes with scorable bands. Primer 60 produced the highest number of bands (8). The highest number of present bands (6) was shown by primer 41 in 10 rice genotypes. Grouping of these genotypes based on the adaptation to agro-climatic zone was not observed, probably due to low percentage coverage of genome by four primers. Most of the genotypes grouped in two clusters. Kali Marsi and IR-24 formed separate individual cluster. Mansara and Jarneli were the most similar landraces (0.96). Churenodhan and Pranpyuri were the most closely related with Masuli. Only one genotype NR-285-18 has fallen in the first quadrant by principal component (PC) analysis and the fourth quadrant was empty. The highest contribution in PC1 was from the second band of primer 41. This RAPD information can be used for selecting lines and for blast resistance breeding. Key words: Genetic distance; rice; RAPD DOI: http://dx.doi.org/10.3126/njb.v2i1.5635 Nepal Journal of Biotechnology Jan.2012, Vol.2(1): 16-25